Integrasi MEREC dan MOORA untuk Pemilihan Ketua OSIS - Oktoverano Lengkong; Edson Yahuda Putra; Ibrena Reghuella Chrisanti (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The selection of a student council president requires an objective assessment process because the decision affects student leadership and the continuity of student programs. At SMK Yadika Manado, the assessment of student council president candidates may still be influenced by subjectivity and requires relatively long processing time when performed manually. This study develops a web-based decision support system for selecting the student council president using a combination of MEREC and MOORA. MEREC is used to determine objective criteria weights based on the removal effect of each criterion, while MOORA is used to rank alternatives using normalized values and criteria weights. The test data consist of three candidates evaluated using four criteria: leadership, responsibility, discipline, and achievement. The results show that responsibility has the highest weight of 0.262295, followed by discipline at 0.252831, achievement at 0.248925, and leadership at 0.235948. The final ranking identifies Keanu Mangundap as the best alternative with a score of 0.672946. The developed system supports candidate data management, criteria management, weight calculation, and transparent ranking presentation.